Recent Developments Regarding Voltage-Gated Sodium Channel Blockers for the Treatment of Inherited and Acquired Neuropathic Pain Syndromes - Theile, Jonathan W.; Cummins, Theodore R. (Frontiers in Pharmacology, 2011)
Chronic and neuropathic pain constitute significant health problems affecting millions of individuals each year. Pain sensations typically originate in sensory neurons of the peripheral nervous system (PNS) which relay information to the central nervous system (CNS). Pathological pain sensations can arise as result of changes in excitability of these peripheral sensory neurons. Voltage-gated sodium channels are key determinants regulating action-potential generation and propagation; thus, changes in sodium channel function can have profound effects on neuronal excitability and pain signaling. At present, most of the clinically available sodium channel blockers used to treat pain are non-selective across sodium channel isoforms and can contribute to cardio-toxicity, motor impairments and CNS side effects. Numerous strides have been made over the last decade in an effort to develop more selective and efficacious sodium channel blockers to treat pain. The purpose of this review is to highlight some of the more recent developments put forth by research universities and pharmaceutical companies alike in the pursuit of developing more targeted sodium channel therapies for the treatment of a variety of neuropathic pain conditions.